ANALYSIS ON MORAL VALUES ON LASKAR PELANGI NOVEL BY ANDREA HIRATA AND ITS UTILIZATION LITERATURE TEACHING MATERIALS IN SENIOR HIGH SCHOOL - dwi Nopiyadi; Rizka Dwiyana; Amanda Shalshabila Putri (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2022)
Various kinds of problems are often experienced by each individual or society which will have an impact on the human person itself even to the surrounding community, one of these problems is a moral problem. The purpose of this study is to describe and explain: (1) the form of moral values in the novel Laskar Pelangi by Andrea Hirata; (2) the views of the author and readers of the novel Laskar Pelangi by Andrea Hirata; (3) utilization as a literature teaching material in high school. This research is a qualitative descriptive research with content analysis method. The data source in this study is the text or content in the novel Laskar Pelangi by Andrea Hirata. Data collection techniques are reading, taking notes and interviews. The validity of the data in this study is source triangulation and method triangulation. The results of this study can be concluded as follows: (1) the form of moral values in the novel Laskar Pelangi by Andrea Hirata, namely (a) the relationship between humans and oneself which includes: honesty, patience, responsibility, sincerity, firmness, courage, and low self-esteem. heart; (b) human relationships with other humans which include: caring for others, helping each other, sharing, caring, encouraging and motivating, working together, being grateful; (c) human relationship with God which includes: gratitude to God, obedient worship, belief in God; (b) human relationships with other humans which include: caring for others, helping each other, sharing, caring, encouraging and motivating, working together, being grateful; (c) human relationship with God which includes: gratitude to God, obedient worship, belief in God; (b) human relationships with other humans which include: caring for others, helping each other, sharing, caring, encouraging and motivating, working together, being grateful; (c) human relationship with God which includes: gratitude to God, obedient worship, belief in God;